Biofilm formation by Aquaspirillum Spp. and Saprophytic Leptospira Spp. isolated from environmental source Of Argentine - Scialfa, Exequiel Alejandro (2019)
Leptospirosis is a zoonotic disease of global distribution, caused by bacteria of the genus Leptospira. These spirochetes are living organisms free of mud and water; pathogenic leptospires can survive several days in fresh water when pH and temperature are adequate. During 2016, water samples were collected from Callvú Leovú stream (Azul, Buenos Aires); samples were inoculated in liquid EMJH medium and incubated at 28° C for 90 days. Six isolates of saprophytic leptospires and six of spirils (Aquaspirillum spp.) were obtained. The isolates were inoculated in EMJH (liquid and semi-solid) medium and sterile stream water at 4-10° C and 28-30° C; development was observed periodically using dark field microscopy. Both bacteria (alone or together) grew exponentially in first three weeks in all media incubated at 28-30° C; the semi-solid medium was the most efficient at 28-30° C of incubation, and the bacteria remained viable after 16 weeks. At 4-8° C both bacteria remained undetectable but viable in media incubated at 4-8° C for three weeks until the temperature was optimal (thermal stimulation). Leptospires developed in all media used and remained viable for 112 to 168 days (at 4-8° C incubation) in liquid media. The formation of cellular aggregate between Leptospira spp. and Aquaspirillum spp. was independent at the incubation temperature. These results suggest that Aquaspirillum spp. coexists with the genus Leptospira in surface waters, and their presence may indicate possible circulation of leptospires.